Evaluasi Penerapan Keselamatan dan Kesehatan Kerja Pada Pengangkutan Overburden dari Front Penambangan Menuju Disposal di PT X Lahat Sumatera Selatan - Sefi Aranda; Reni Arisanti; Ahmad Husni (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Overburden transportation constitutes a critical stage in open-pit mining operations, characterized by a high level of safety risk and a direct influence on production continuity. This study aims to evaluate the implementation of Occupational Safety and Health (OSH) in overburden hauling activities from the mining front to the disposal area at PT X, Lahat Regency, South Sumatra. The research employed a descriptive design integrating qualitative and quantitative approaches. Data were collected through field observations, interviews with relevant stakeholders, questionnaires administered to workers and heavy-equipment operators, and hazard identification alongside risk assessment using the Risk Assessment Matrix. The findings indicate that OSH implementation at PT X can be classified as satisfactory, as reflected in the high level of compliance with personal protective equipment usage, routine safety briefings, adequate safety signage, and active supervision by OSH personnel. Risk analysis shows that most hauling activities fall within low to moderate risk categories, although several hazards still require additional control measures. Overall, the OSH system in overburden transportation operates effectively; nevertheless, continuous evaluation remains essential to enhance operational safety and further reduce accident potential.